2021
DOI: 10.47836/pjssh.29.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Support from Lecturers and Host Country Nationals on Cross-Cultural Adjustment among International Students: Evidence from a Malaysian University

Abstract: Pursuing higher education abroad is a golden opportunity for any student’s personal development; however, international students’ cross-cultural adjustment (CCA) can be onerous in a foreign country. The purpose of this study is to empirically examine the roles of perceived lecturer support and host country national (HCN) support in international students’ CCA in three dimensions, i.e. general, academic, and interaction. Adopting the purposive sampling technique, survey data was collected from a sample of 124 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Further misunderstanding between the two cultures increases uncertainty and decrease satisfactory intercultural interaction (Rajan et al, 2021). While a previous study indicated the effect of lecturer to reduce uncertainty and increase intercultural adjustment in international students (Chan et al, 2021), the teaching and relationship of Finnish teachers with students is not satisfactory for Iranian students. In addition, access to information on Finnish university websites does not seem to meet the needs of international students, however none of them causes students concern because of the possibility of asking others (Hosseini et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Further misunderstanding between the two cultures increases uncertainty and decrease satisfactory intercultural interaction (Rajan et al, 2021). While a previous study indicated the effect of lecturer to reduce uncertainty and increase intercultural adjustment in international students (Chan et al, 2021), the teaching and relationship of Finnish teachers with students is not satisfactory for Iranian students. In addition, access to information on Finnish university websites does not seem to meet the needs of international students, however none of them causes students concern because of the possibility of asking others (Hosseini et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Further misunderstanding between the two cultures increases uncertainty and decrease satisfactory intercultural interaction (Rajan et al, 2021). While a previous study indicated the effect of lecturer to reduce uncertainty and increase intercultural adjustment in international students (Chan et al, 2021), the teaching and relationship of Finnish teachers with students is not satisfactory for Iranian students. In addition, access to information on Finnish university websites does not seem to meet the needs of international students, however none of them causes students concern because of the possibility of asking others .…”
Section: Discussionmentioning
confidence: 86%
“…There are numerous challenges and difficulties that Malaysian undergraduates face while realizing their universities' implementation of international community service programmes during their university life. The previous study discovered the challenges and difficulties that undergraduates face include inadequate proper training, insufficient institutional support, and financial constraints (Othman & Ahmad, 2017;Bista & Foster, 2018;Cheong et al, 2018). Besides, Malaysian undergraduates are facing additional challenges such as adapting to the local culture (Lim et al, 2019) and language barriers (Muhammad et al, 2017).…”
Section: Literature Review International Community Servicementioning
confidence: 99%